2013
DOI: 10.3748/wjg.v19.i21.3207
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical-treatment patterns and outcome in 256 hepatocellular carcinoma cases

Abstract: This study showed that, between 2000-2005 and 2005-2010, the number of HCV-related HCC decreased, non-viral/non alcoholic etiologies increased and of surveillance programs were more frequently applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
7
16
2
Order By: Relevance
“…The peak age of incidence of HCC was found to be in older population with mean age 65 years, which is in line with the recently published data from Saudi Arabia [ 22 ] and countries like Italy [ 29 ], Japan [ 30 ], and Portugal [ 31 ]. However, this is fairly different from the average age as reported in the latest US literature, which was between 57 and 59 years [ 32 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…The peak age of incidence of HCC was found to be in older population with mean age 65 years, which is in line with the recently published data from Saudi Arabia [ 22 ] and countries like Italy [ 29 ], Japan [ 30 ], and Portugal [ 31 ]. However, this is fairly different from the average age as reported in the latest US literature, which was between 57 and 59 years [ 32 34 ].…”
Section: Discussionsupporting
confidence: 88%
“… 1 Because of early angioinvasion and metastasis, only a small proportion of patients with hepatocellular carcinoma (HCC) receives surgical resection or liver transplantation as a curative treatment. 2 Except for sorafenib, a multikinase inhibitor, there are no effective systemic treatments of HCC. Two large phase III randomized controlled trials showed that the median overall survival was 10.7 months 3 and 6.5 months 4 in a sorafenib-treated group.…”
Section: Introductionmentioning
confidence: 99%
“…HCV accounts for over one-third of the cases of HCC in the USA (Davila) and around 90% of these patients have underlying cirrhosis or advanced fibrosis [20]. Over the past decade, the number of HCC cases related to NASH has been increasing [21]. In multivariate analysis, the investigators have identified four factors predictive for development of HCC; those include age, male gender, albumin and low platelet count.…”
Section: Discussionmentioning
confidence: 99%